Bunkerproblematik med avseende på flödesmätning - Olsson, Edvin; Lundgren, Johan (My University, 2014)
This thesis is about the bunker problems regarding flow measurement. Bunker problems mainly consist of quantity- and quality problems. The authors have limited this thesis to the quantity problems which got the authors attention during vocational training. These problems may be due to measurement methods, equipment, external influences and different interests of both buyers and sellers. As the bunker costs account for 50-70 % of the operational costs for a vessel it should be in the shipping company interest to gain better control of their bunker deliveries. The authors have investigated in which way it is relevant for a vessel to install a mass flow meter to measure the received bunker. To explore the subject a literature search was made supplemented by interviews with the shipping industry. The result shows that it is not relevant to install a mass flow meter on board a vessel. Mainly because it is the bunker supplier's quantity figures that are final at any quantity dispute. Mass flow meters can be a good analysis and monitoring tool for the ship owners to get an easier overview of the received bunker. Mass flow meter is now used by ship owners and bunker suppliers, though in a small scale and with varying results. What is missing is an international standard that sets the ground rules for how the mass flow meter shall be used for bunker operations. The technology already exists today and is capable of measuring the bunker with high accuracy. Why not use this tool to make bunker procedures easier for both buyers and sellers?
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport